Technological turbulence as hindrance between factors influencing readiness of senior management and implementing blockchain technology in Jordanian Islamic banks: A structural equation modeling approach - Ibrahim Radwan Alnsour (Journal of Innovation and Entrepreneurship, 2024)
The purpose of the study was to identify the factors that influence senior management for adopting blockchain technology in the banking industry in general and Islamic banking in particular. Furthermore, the research addressed the moderating role of technological turbulence as it holds a significant hindering role. This study employed the analytical approach, and the data were collected through questionnaires distributed to several senior management employees in both the Jordan Islamic Bank and the Islamic Arab Bank. The research instrument was developed and confirmed by the experts in the field. For identifying the significance of the variables incorporated in the researchers applied structural equation modeling technique. The findings revealed that economic efficiency, bank security, customer expectations, education, training and preparation all are significant predictors of readiness for implementing blockchain technology in the Islamic banks in Jordan. The study concluded that blockchain technology should be adopted by all Islamic banks because of its advantages and also the management needs to be educated regarding the same; they should be provided appropriate training.
Keywords: 650; Blockchain technology; Islamic banking; Legitimate interest; Private interest; Technological turbulence